2022
DOI: 10.3390/jof8060597
|View full text |Cite
|
Sign up to set email alerts
|

The Biogenically Efficient Synthesis of Silver Nanoparticles Using the Fungus Trichoderma harzianum and Their Antifungal Efficacy against Sclerotinia sclerotiorum and Sclerotium rolfsii

Abstract: Silver nanoparticles (AgNs) are known as a promising alternative tool to control fungal diseases. AgNs were biologically synthesized using Trichoderma harzianum filtrate as an ecofriendly approach. The presence of AgNs was confirmed by changing the color to brown, followed by UV-Vis spectroscopy, transmission electron microscopy (TEM), and Energy-dispersive spectra (EDS). TEM studies showed that the size of AgNs average was 31.13 nm and the shape was spherical. In vitro assays of AgNs showed a significant inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…The effect of diverse NPs on the linear growth and reduction percentage of S. cepivorum provides insights into potential antifungal strategies [43]. The findings align with previous studies on the antifungal properties of nanoparticles.…”
Section: Discussionsupporting
confidence: 84%
“…The effect of diverse NPs on the linear growth and reduction percentage of S. cepivorum provides insights into potential antifungal strategies [43]. The findings align with previous studies on the antifungal properties of nanoparticles.…”
Section: Discussionsupporting
confidence: 84%
“…Recent studies have demonstrated that AgNPs fabricated using pomegranate peel, Trichoderma harzianum , Grass waste, and strawberry waste were effective against A. solani , S. sclerotiorum, F. solani , and F. oxysporum , respectively ( Khatami et al, 2018 ; Khan et al, 2021 ; Mostafa et al, 2021 ; El-Ashmony et al, 2022 ). A. digitata based-FeONPs were effective against Alternaria sp, S. sclerotiorum, F. venenatum , and F. equiseti at ( P < 0.0001) except against Fusarium sp.…”
Section: Resultsmentioning
confidence: 99%
“…To tackle these problem, efficient alternatives are being investigated & explored as use of biocontrol agent seems to be a hopeful approach. In addition to other biocontrol agents, Trichoderma harzianum has proved to be very effective in controlling plant pathogens (El-Ashmony et al, 2022). Various mechanisms have been evolved in Trichoderma spp.…”
Section: Discussionmentioning
confidence: 99%